The hedgehog effect executive coaching and the secrets of building high performance teams - Manfred F. R Kets de Vries (San Francisco Jossey-Bass, 2011)
In The Hedgehog Effect, Manfred Kets de Vries presents the case for leadership group coaching as an experiential training ground for learning to function as a high performance team. His group coaching model, incorporating living case studies, has been developed over more than 20 years of delivering programs to top-level executives and sets the standard in the field of leadership group coaching.
Includes bibliographical references and index
Keywords: Teams in the workplace -- Management; Employees -- Coaching of; Leadership; Organizational change